RF Tuning Micro Cantilever Array Design, Modeling, and simulation - Kafumbe, Said; Alun Harris, Jim Burdess (IEOM Society International, 2018)
MEMS cantilever arrays can be used as non-destructive alternatives during frequency tuning applications. This is because a small electrostatic voltage applied between the cantilever and the bottom electrode is enough to pull it down. Further perturbations can be used to resonate the beam at a different frequency. However, before such micro cantilevers can be designed and fabricated, analytical and numeric modelling and simulation is helpful in the validation of the concept. This paper presents the modelling and simulation of MEMS cantilevers that are used in frequency tuning applications.
Keywords: MEMS; cantilevers; electrostatic actuation; piezo electric actuation; modelling; simulation